Interactive storytelling elements in R. L. Stine’s “Give Yourself Goosebumps #2: Tick Tock, You’re Dead!” - Yohana Aurilia Binambuni; Didit Kurniadi; Eko Heriyanto (Universitas Aki, 2024)
This study explores the captivating world of interactive storytelling, focusing on how it brings horror narratives to life through the lens of R.L. Stine’s “Give Yourself Goosebumps #2: Tick Tock, You’re Dead!”. With storytelling evolving in the digital age, this study aims to unravel the elements behind what keeps readers hooked. This study uses qualitative descriptive method, specifically using literary analysis approach, dissecting the novel to uncover hidden gems and patterns. This study shows that interactive storytelling within horror narrative is not just about scaring the readers—it is a powerful tool that entertains, challenges, and inspires readers and authors alike. This study touches on interactive storytelling elements such as decision points, reader agency, consequences of choices, multiple storylines, and replay-ability, these techniques add layers to the horror narrative experienced by the readers.